2015
DOI: 10.1039/c4cs00456f
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous dye-sensitized solar cells

Abstract: Nowadays, dye-sensitized solar cells (DSSCs) are the most extensively investigated systems for the conversion of solar energy into electricity, particularly for implementation in devices where low cost and good performance are required. Nevertheless, a key aspect is still to be addressed, being considered strongly harmful for a long time, which is the presence of water in the cell, either in the electrolyte or at the electrode/electrolyte interface. Here comes the present review, in the course of which we try … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
292
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 405 publications
(298 citation statements)
references
References 332 publications
(423 reference statements)
5
292
0
1
Order By: Relevance
“…The fundamentals and concept of PEC have been well developed in 1970s, based on which the dye-sensitized solar cell (DSSC) and PEC water splitting are stimulated by the energy crisis during the 1970-1980s [6][7][8][9][10][11]. Ever since, many researchers have made great efforts to promote the PEC solar production, especially the PEC water splitting for H 2 production, targeting a solar-to-hydrogen (STH) efficiency of 10 % for commercial application [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The fundamentals and concept of PEC have been well developed in 1970s, based on which the dye-sensitized solar cell (DSSC) and PEC water splitting are stimulated by the energy crisis during the 1970-1980s [6][7][8][9][10][11]. Ever since, many researchers have made great efforts to promote the PEC solar production, especially the PEC water splitting for H 2 production, targeting a solar-to-hydrogen (STH) efficiency of 10 % for commercial application [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, water as the most abundant and benign solvent on Earth and is ideal for the preparation of DSC electrolytes; several research groups have recently turned their interest toward this direction [55,70,[90][91][92][93][94]. Another drawback, typical of quasi-solid DSCs, concerns the effect of the poor penetration of gel electrolytes into the mesoporous photoanodes [95].…”
Section: Aqueous Electrolytes: An Emerging Approach To Stabilize Cobamentioning
confidence: 99%
“…On exposure to light, the dye molecules are almost depleted within 200 h in the presence of Li + , which is much faster than in the presence of EIm + or on exposure to heat. Moreover, since water had previously been shown to play an important role in dye degradation [55] and considering that Li + salts are hygroscopic, a dehydrated Li + salt was employed for comparison. A difference in the early rate due to the addition of Li + ions was noted, but not in the total amount of dye degradation when the same amount of water was added.…”
Section: Liquid Electrolytes: Tuning Of Cobalt Complexes' Chemical Stmentioning
confidence: 99%
“…In overall, the results of EIS (increase in the charge transfer resistance, and decrease in the admittance and capacitance values due to the application of α-NZF pigment) showed that in the presence of the as-synthesized pigments, especially α-NZF sample, the inhibition performance was improved significantly relative to metal immersed in blank solution. This may be related Potency of ZnFe 2 O 4 Nanoparticles as Corrosion Inhibitor for Stainless Steel; the Pigment Extract Study to replacement of nanopigments with water molecules 44 and increasing the thickness of electrical double layer and inhibitor film due to NZF adsorption increment on mild steel surface during immersion time 39 . Figure 4 compares the polarization results for the samples immersed in the test solutions after 1, 4 and 44 h. The resulted data of Tafel polarization measurements are listed in Table 3.…”
Section: Eis Measurementsmentioning
confidence: 99%